DETERMINATION THE BEGINNING OF QAMARIYAH MONTH ACCORDING TO GOVERNMENT - Watni Marpaung; Nurhayati Nurhayati (Islam Futura, 2019)
This paper describes about the issue of determining the beginning of the month of Qamariyah according to the government perspective. This study is important because it is related to the dynamics of the determination of the beginning of the Qamariyah month which is quite complex. In the history of determining the beginning of the month of Qamariyah in Indonesia, there was a recurring difference in determining the beginning of the month of Qamariyah. This condition is motivated by a concept that is understood and embraced by the Indonesian people which refers to two large patterns between the use of computation and rukyat (seeing the moon). Moreover, the pattern of understanding of community organizations. In the concept of computation is divided  into patterns and techniques used, such as urfi computation, true computation. In the context of this difference, essentially the government has been present to bridge the difference in the results of the determination of the beginning of the Qamariyah month from the rukyat and computation techniques with itsbat hilal. This concept actually to concocts two major view between computation (hisab) and rukyat with the specified criteria